Penerapan Numbered Heads Together Untuk Meningkatkan Aktivitas Dan Hasil Belajar PKn Pada Siswa Kelas V SD - Amimah Nur (Universtas Negeri Makassar, 2022)
This research is CAR using the Kemmis and Mc Taggart model which is carried out in two cycles. Each cycle consists of stages of planning, action, observation, and reflection. The subjects of this study were students of Class V SD Inpres Garongkong 02, totaling 29 students consisting of 12 male students and 17 female students. Analysis of the data used in this study with completeness analysis and comparative descriptive analysis that is comparing the learning outcomes of pre-cycle, cycle 1 and cycle 2. 79.31% with less criteria, cycle 1 there was an increase of 67.24% with sufficient criteria, complete learning outcomes as many as 19 students (65.51%) were completed, the highest score was 87, and the lowest score was 67. Cycle 2 showed increased learning activity to be 87.92% with very good criteria, complete learning outcomes as many as 25 students (86.21%) were completed, the highest score was 100, the lowest score was 73.